2020
DOI: 10.1186/s13049-020-0699-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific complaints in the emergency department – a systematic review

Abstract: Background Nonspecific complaint (NSC) is a common presenting complaint in the emergency setting, especially in the elderly population. Individual studies have shown that it is associated with significant morbidity and mortality. This prognostic systematic review draws a synthesis of reported outcomes for patients presenting with NSC and compares them with outcomes for patients presenting with a specific complaint. Methods We conducted a literature search for publications, abstracts and conference presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 39 publications
2
26
1
4
Order By: Relevance
“…The most common code was weakness/tiredness, general (A04), seen in 13.5% of all patients. This is in concordance from recent finding from emergency departments [39]. Overall, it also seems that traditional high risk patient groups such as "first hour quintet" [40] represent a small minority of all patients encountered by the EMS.…”
Section: Discussionsupporting
confidence: 90%
“…The most common code was weakness/tiredness, general (A04), seen in 13.5% of all patients. This is in concordance from recent finding from emergency departments [39]. Overall, it also seems that traditional high risk patient groups such as "first hour quintet" [40] represent a small minority of all patients encountered by the EMS.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with these diagnoses were commonly triaged to the RETTS-A category of non-specific complaints. Previous studies have shown that elderly patients with non-specific complaints in the ED have a higher short-term mortality, are to be triaged as less urgent and require resources and hospitalisation to a greater extent than patients with specific complaints [37,38]. There is also a risk of patients being referred to other levels of care with the aid of a triage system, with older patients being more frequently triaged to non-specific complaints than younger patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…With great interest we have read the recent systematic review on "Nonspecific Complaints (NSCs) in the Emergency Department" [1] and would like to comment on two key aspects: First, we agree that NSCs should be considered a major emergency presentation. Different nomenclatures have been used in the past, such as "homecare impossible", "unexplained symptoms", "general disability", "atypical symptoms", and "nonspecific functional decline" (for review, see [2]).…”
Section: Dear Editormentioning
confidence: 99%